PERBAIKAN KUALITAS CITRA BAWAH AIR DENGAN ALGORITMA MSRCR (MULTISCALE RETINEX WITH COLOR RESTORATION) - Asri, Sri Dianing (Jurnal Teknoinfo, 2024)
The underwater environment has high complexity, which naturally arises due to the absorption and scattering of light waves by water and other particles suspended in it. This results in underwater images with low contrast, blurriness, and unclear details, necessitating the use of image enhancement methods. The Retinex method aims to maintain color constancy, where the color of an object appears relatively the same even under different lighting conditions. Preliminary research indicates that the SSR and MSR methods still produce halo effects. Therefore, this study modifies and enhances the MSR method by adding color restoration to correct the color distortion caused by water. This research begins with test images of 5 x 5 dimensions. The image enhancement process is conducted using the proposed MSRCR method and then analyzed mathematically on digital images. Subsequently, it is applied to underwater images with different sigma (